Some Health Effects of Exposure to Static Magnetic Fields and Radiofrequency Energy among MRI Staff Working with 1.5 and 3.0 Tesla Scanners in South Africa (African Journal of Biomedical Research, 2020)
Occupational exposure to magnetic resonance imaging (MRI)-related electromagnetic fields is associated with the development of adverse and transient health effects. The aim of this study was to assess the health effects associated with exposure to Static Magnetic Fields (SMFs) and radiofrequency (RF) energy amongst MRI staff in 1.5 and 3.0 T MRI units. Data were collected through questionnaires completed by 42 MRI staff members working in Hospital A (57.89%) and Hospital B (42.11%) in the Mangaung metropolitan region. Of the participating staff, four did not indicate the facilities in which they worked. Twenty-four of the participants were female and eighteen were male, and their mean age was 37 years (range of 20 to 61). The questionnaire was categorized in terms of the participants’ biographical, work, and health-related information. Radiographers (35.71%), student radiographers (11.9%), nurses (9.52%), medical physicists (4.76%), maintenance engineers (4.76%), radiologists (9.52%), and cleaners (23.81%) working in both hospitals participated in the study. The data was analysed to determine the percentages and frequencies for the categorical data. Of the 42 participants, 30.95% reported hypertension, 11.9% reported hypotension, 2.38% reported cataracts, 16.67% reported depression, and 16.67% reported increased heart rates as a priori-unrelated health effects. Regarding priori-related health effects, 26.19% of the participants reported a metallic taste, 40.48% reported vertigo, 21.43% reported nausea, 7.14% reported hypothermia, 2.38% reported hyperthermia, 19.05% reported concentration difficulties, 21.43% reported blurred vision, and 19.05% reported vitamin deficiencies. Vertigo was reported to be the most common SMF exposure-related effect. Of the 61.9% of MRI staff who wore PPE, 30.77% were found to wear MRI-related PPE when working in the MRI units. The results reported in this study were found to be consistent with the exposure-related effects of MRI units investigated in many other studies. The results also suggest future studies that could determine the association between exposure and the development of depression and cataracts in a larger study population of MRI workers
Keywords: Health effects of MRI scanners; exposure assessment; 1.5 and 3 T scanners